ESTIMATING CLAIM RESERVE IN GENERAL INSURANCE - KADRI ALI (NIM: 10114017), JERRI
Claim reserve is an estimate of the value of a claim or group of claims not yet paid. In this Final Project claim reserve and its standard error in general insurance estimated using Mack Chain Ladder method. Mack Chain Ladder method use data with run-off triangle format. First, the concepts necessary to use the Mack Chain Ladder are explained. Then, the method is applied to the regular run-off triangle data obtained from Taylor and Ashe (1983) and irregular run-off triangle data. The results will be compared with the results obtained through the Vector Projection method. It can be concluded even though Mack Chain Ladder method is the most popular method used among actuaries but the method still has deficiencies when the data used does not meet the assumption so that resulting a large standard error.